Early years, family and education task group: report European review of social determinants of health and the health divide in the WHO European Region - Jensen, B; Currie, C; Dyson, A; Eisenstadt, N; Melhuish, E (WHO Europe, 2013)
The task group on early years, childhood and family was set up as part of the European review of social determinants of health and the health divide in the WHO European Region, which was commissioned to support the development of the new health policy framework for Europe, Health 2020. The task group was asked to identify interventions, strategies and approaches that policy-makers and practitioners in the Region can use in the childhood years to improve and equalize health outcomes throughout the life-course. The report’s analysis is organized in terms of early years and later childhood to reflect phases of children’s experience that are distinct in many ways and which require different forms of service provision. Evidence comes from the international research evidence, a review of reports from transnational organizations, and case studies of illuminating practice from European countries. The report’s broad conclusions should be considered in conjunction with more detailed recommendations provided throughout the text.